Analisa Komparasi Penanganan Kasus Kejahatan Transnasional Biopiracy antara India dan Amerika Serikat di Bawah Rezim Internasional - Anggraeni Maulia Vidyastutie; Ika Riswanti Putranti; Andi Akhmad Basith Dir (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Biopiracy is a crime that generally involves multinational corporations with indigenouscommunity regarding the copyright of over the natural resources. This crime often escapesattention while the effects are very dangerous for the survival of a country’s indigenouscommunity. This study aims to find out how biopiracy actually becomes a dangeroustransnational crime and how developed and developing countries represented by theUnited States and India deal with this crime from the perspective of their respectivecountries under the international regime. The author uses the theory of Cultural Relativismand Social Planning to analyze the handling done by the United States and India. Thisstudy will analyze the history of the two countries, how the two countries understand themeaning of biopiracy, and the position of the two countries under the international regimerelated to the handling of transnational biopiracy crime cases